Binary Template Matching for Morphological Dilation Enhancement in Navigation Radar Imaging - Octa Heriana; Teguh Praludi; Chaeriah Bin Ali Wael (Jurnal Elektronika dan Telekomunikasi, 2018)
Radar imaging system is strongly influenced by other supporting systems. There is a motor system that provides angular information to the display system, and Digital Signal Processing (DSP) system that provides the main information for radar imaging. The new approach, we substitute a DC servo motor with a DC stepper motor as radar antenna rotator in our navigation radar system development. Different from the use of servo motors that can provide angle movements smoothly, the new motor system provides angle information of 0.56 degrees in every step, results in empty pixel gaps in every 0.56 degrees in radar Plan Position Indicator (PPI) image. The width of the empty pixel gaps becomes wider when the cell array of raw data is increasing regarding the image plotting process. In this paper, we proposed a new morphological dilation method to the radar raw data based on binary template matching to accommodate the various width of empty pixel gaps before the radar raw data are plotted into the radar PPI image. By this method, the morphological dilation will only be applied to the raw data that meet the same criteria as the binary template. Otherwise, the raw data will be left as they are. The result shows that there is 150.52% pixel data addition in the empty pixel gaps from the original image, and 48.44% increase of the morphological dilation without binary template matching method.